Relevance of chronic stress and the two faces of microglia in Parkinson’s disease - Herrera, Antonio J.; Espinosa-Oliva, Ana M.; Carrillo-Jiménez, Alejandro; Oliva-Martín, María J.; García-Revilla, Juan; García-Quintanilla, Alberto; de Pablos, Rocío M.; Venero, José L. (Frontiers in Cellular Neuroscience, 2015)
This review is aimed to highlight the importance of stress and glucocorticoids in modulating the inflammatory response of brain microglia and hence its potential involvement in Parkinson’s disease. The role of inflammation in Parkinson’s disease has been reviewed extensively in the literature and it is supposed to play a key role in the course of the disease. Historically, glucocorticoids have been strongly associated as anti-inflammatory hormones. However, accumulating evidence from the peripheral and central nervous system have clearly revealed that, under specific conditions, glucocorticoids may promote brain inflammation including pro-inflammatory activation of microglia. We have summarized relevant data linking Parkinson’s disease, neuroinflamamation and chronic stress. The timing and duration of stress response may be critical for delineating an immune response in the brain thus probably explaining the dual role of glucocorticoids and/or chronic stress in different animal models of Parkinson’s disease.